Evaluation of the antiulcer and antimicrobial activities of methanol leaf extract of Helianthus annuus - Ajegi, Innocent F.; Ajegi, Gloria O.; Ajaegbu, Obinna C.; Nwokike, Matthew O.; Ramalan, Mansur A.; Eje, Victor I.; Akuodor, Godwin C. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Medicinal plants are widely used in treating and preventing specific diseases and are known to play an important role in health care. Helianthus annuus is one of such plants whose therapeutic applications no doubt have numerous folkloric background. This study aimed at assessing Helianthus annuus methanol leaf extract for antiulcer and antimicrobial potentials Methods: The antiulcer activity was evaluated using aspirin, ethanol and histamine methods in Wistar rats, while the antimicrobial activity was carried out on selected microorganisms. The acute toxicity test and phytochemical screening of the extract were also conducted. Results: The methanol leaf extract exhibited significant (p<0.05 and p<0.01) antiulcer effect in both model. The ulcer protection effect of the extract is comparable to omeprazole. The extract also significantly inhibited the growth of test organisms. The acute toxicity test produced no lethality in rats, whereas the phytochemical analysis revealed the presence of alkaloids, saponins, tannins, flavonoids, terpenoids and steroids. Conclusions: The findings confirm the ethnomedicinal use of H. annuus leaf as a valuable natural agent for the treatment of ulcer and microbial infections.